2001
DOI: 10.1159/000046898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halothane, Pentobarbital and Ketamine on Serum Melatonin Levels in the Early Scotophase in New Zealand White Rabbits

Abstract: In mammals, the nocturnal rise in pineal melatonin is regulated by signals from the endogenous clock, the hypothalamic suprachiasmatic nuclei. There have been few reports on whether anaesthetics which modulate multisynaptic neuronal functions affect melatonin secretion. We studied the effects of three commonly used anaesthetics, halothane, pentobarbital and ketamine, on serum melatonin levels in male New Zealand white rabbits. Seven blood samples were collected, 30–60 min apart, before, during and after anaest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…28 In animal studies, ketamine was shown to potentiate the release of melatonin whereas halothane did the opposite. 29 Melatonin demonstrated beneficial results in children in attenuating emergence agitation following sevoflurane anaesthesia. 30 One of the limitations of the current study is the absence of a placebo-controlled group.…”
Section: This Article Has Been Retractedmentioning
confidence: 99%
“…28 In animal studies, ketamine was shown to potentiate the release of melatonin whereas halothane did the opposite. 29 Melatonin demonstrated beneficial results in children in attenuating emergence agitation following sevoflurane anaesthesia. 30 One of the limitations of the current study is the absence of a placebo-controlled group.…”
Section: This Article Has Been Retractedmentioning
confidence: 99%
“…It can easily distribute to the tissues because it is liposoluble [2]. Therefore stressors such as surgery or pain and agents causing sympathetic nerve excitation can change melatonin levels [11]. Inhalational anesthetics, especially desflurane, are known to have sympathetic nerve excitation effects [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…[25] Melatonin demonstrated beneficial results in children, in attenuating emergence agitation following sevoflurane anesthesia. [26]…”
Section: Discussionmentioning
confidence: 99%